From talking to the radio to talking through the radio: Addressee analysis of text messages sent to the Italian radio station. (August 2017) - Zelenkauskaite, Asta
Abstract: This study analyzes addressee choice(s) in text message construction sent to the radio station by listeners. Addressee choices within a text message are conditioned by the user texting practices implemented by the radio station in several ways. First, the radio station filters listeners' messages and does not text back. Second, texting is limited to a character length. Thus, messages have to be relevant but succinct. Study has revealed that texters addressed their messages one to another instead of addressing their messages to the radio station; this occurred in single and multiple-addressee messages. This finding suggests that listeners continue to address the radio station, as in classical call-ins, yet, these practices reveal the shift from talking to to talking through mass media. This research suggests that individual audience members' engagement with mass media shifts toward interpersonal uses of back-channels that are not necessarily geared toward mass media content. I explain such behaviors through the lens of associational listening that fosters interpersonal talk. The emergence of messages that combines radio and user addressees resemble what we metaphorically call interactive content smuggling geared toward interpersonal interactions through a mass medium.